2016
DOI: 10.1002/ijc.30281
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behavior in relation to lung cancer incidence and mortality in older women: The Women's Health Initiative

Abstract: Physical activity has been associated with lower lung cancer incidence and mortality in several populations. We investigated these relationships in the Women’s Health Initiative Observational Study (WHI-OS) and Clinical Trial (WHI-CT) prospective cohort of postmenopausal women. The WHI study enrolled 161,808 women aged 50–79 years between 1993 and 1998 at 40 U.S. clinical centers; 129,401 were eligible for these analyses. Cox proportional hazards models were used to assess the association of baseline physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 58 publications
6
37
0
Order By: Relevance
“…Results did not differ, so presented results are from analyses in which women were assigned a value of 0. We evaluated both time spent sitting and total sedentary time to be consistent with previous WHI-OS reports that investigated total sedentary time [24,22,23,32]. However, results did not differ when using total sitting time compared to estimated total sedentary time as the measure of sedentary time exposure.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…Results did not differ, so presented results are from analyses in which women were assigned a value of 0. We evaluated both time spent sitting and total sedentary time to be consistent with previous WHI-OS reports that investigated total sedentary time [24,22,23,32]. However, results did not differ when using total sitting time compared to estimated total sedentary time as the measure of sedentary time exposure.…”
Section: Methodsmentioning
confidence: 78%
“…Previous analyses in the WHI-OS suggest sedentary time may be associated with chronic disease outcomes [24,22,23,32]. Time spent sitting was reported to be associated with all-cause, cardiovascular disease, coronary heart disease and cancer mortality, independent of recreational physical activity [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One meta-analysis that estimated the association among women separately found an overall relative risk of 0.73 (95% CI 0.63-0.86); however it included both case-control and cohort studies, and the heterogeneity between the studies was found to be high (I-squared = 50.9%) [16]. Based on cohort studies that included sex-adjusted analysis and/or specific analysis of women, five found inverse associations [21,22,[40][41][42], while 12 others [19,23,[36][37][38][39][43][44][45][46][47][48][49] found no association between the risk of lung cancer and PA level (including both recreational and non-recreational PA). The suggested mechanisms of PA in protecting against lung cancer is through increase in enzymatic systems that detoxify chemical carcinogens and in this way protect the lungs [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of 28 observational studies, Brenner and colleagues [8] found an inverse association between recreational physical activity and lung cancer risk (relative risk (RR), 0.76; 95% confidence interval (CI), 0.69-0.85). Furthermore, physical activity levels are also associated with lower lung cancer mortality (low physical activity, hazard ratio (HR) 0.80 (0.69-0.92); medium physical activity, HR 0.68 (0.59-0.80); and high physical activity, HR 0.78 (0.66-0.93)) [9]. Similar evidences have been published regarding fruits and vegetables intake (RR 0.86; 95% CI 0.78-0.94) [10].…”
Section: Introductionmentioning
confidence: 99%